Peningkatan kompetensi profesional guru SD melalui pelatihan pengembangan Iceberg matematika realistik berbasis budaya lokal - Palupi, Evangelista Lus Windyana; Ekawati, Rooselyna; Kohar, Ahmad Wachidul; Mubarkah, Resti Elmi; Kartikawati, Wahyu; Purbaningrum, Mayang (Universitas Hamzanwadi, 2023)
Mathematics education needs to be taught meaningfully using problem contexts and facilitating reasoning, modeling, collaboration, and connection with other mathematical concepts. This community service project aimed to train primary school teachers in developing Realistic Mathematics Education (RME) 'icebergs' utilizing the local cultural context of Magetan. Twelve primary school teachers in Magetan participated in the RME training, which focused on developing the RME 'icebergs' through exploratory and contextual approaches. The research method included face-to-face sessions, group discussions, and individual tasks to design relevant learning materials. The training results showed significant improvement in the understanding and application of RME. Before the training, teachers faced challenges in engaging students in grades 4-6 and in using local context in mathematics teaching. Post-training, 67% of the teachers demonstrated a positive change in their teaching approach, shifting from lecture and drill methods to an RME-based approach. Additionally, 50% of the participants successfully developed RME icebergs that integrated problems within the local cultural context of Magetan. The training evaluation indicated that over 50% of participants responded positively, showing increased knowledge about realistic mathematics and the application of culturally contextualized problems. The conclusion of this study asserts that the RME approach, especially when combined with local cultural context, is effective in enhancing mathematics teaching skills and enriching numeracy literacy among primary school teachers. The implications of this research suggest integrating RME into the primary school mathematics curriculum to develop critical thinking, creativity, and collaboration skills in students, in line with the demands of the 21st century.